GASTRONOMIC TOURISM IN THE REPUBLIC OF MOLDOVA - TRENDS AND OPPORTUNITIES - Liliana STAVER; Larisa DODU-GUGEA; Nicolae STANCIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In recent years, gastronomic tourism in the Republic of Moldova has gained momentum due to the country's rich culinary heritage and traditional dishes. The culinary culture of the Republic of Moldova is shaped by its history and geography, with influences from neighbouring countries Romania and Ukraine, as well as its history of being a part of the USSR. The Moldovan wine industry has also played a significant role in driving food tourism, with a long history of winemaking and numerous vineyards and wineries. Moreover, there is growing interest in agri-tourism, which offers visitors the chance to experience rural life and learn about traditional farming practices. Many small family farms in Moldova provide accommodations and activities such as cooking classes, farming activities, and vineyard visits. Despite the potential for food tourism, Moldova's food tourism industry has yet to reach its full potential. To attract more food tourists, promoting and marketing the country's culinary heritage and traditional dishes, as well as increasing the number of food-related events and activities, could prove beneficial. Gastronomy is an integral part of every community, representing a valuable tourism resource and an essential tool for destination image and branding. This paper aims to analyze the potential of Moldova's food tourism industry and provide recommendations for establishing and developing it further as an important pillar of the country's tourism industry. Moldova's ethnic and social diversity and indigenous communities influence its gastronomy, providing insights into ancient gastronomic traditions, customs, manners, and farming practices, making Moldova a unique and underdeveloped gastronomic tourism destination. Materials and methods: The authors apply a quantitative research approach, analyzing data from the National Bureau of Statistics of the Republic of Moldova to examine trends and opportunities in the country's gastronomic tourism. Various research methods, including analysis, comparison, grouping, and SWOT analysis, were employed. Main results: The findings reveal that Moldova's tourism industry was significantly impacted by the COVID-19 pandemic in 2020 but showed signs of recovery in 2021. The country's rural areas, wine industry, and culinary traditions offer unique opportunities for gastronomic tourism development. However, challenges such as lack of awareness, promotion, limited infrastructure, and low stakeholder collaboration need to be addressed. Conclusions: This study highlights Moldova's potential for gastronomic tourism development. To fully develop this industry, efforts should focus on promoting the country's culinary heritage, increasing food-related events and activities, improving infrastructure and services, fostering collaborations, and leveraging digital platforms. By addressing challenges and capitalizing on opportunities, Moldova can establish and further develop its food tourism industry, contributing to economic growth, job creation, and the promotion of its unique culinary heritage.